2016
DOI: 10.1016/j.colsurfb.2016.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone loaded nanostructured lipid carrier gel for effective treatment of mild and moderate acne vulgaris: A randomized, double-blind, prospective trial

Abstract: Spironolactone (SP) known as an anti-androgen drug, has been proven to be effective in treatment of acne. The quest to minimize the unnecessary systemic side effects associated with the oral drug administration of spironolactone, has led to a growing interest of loading SP on lipid nanoparticles to deliver the drug in a topical formulation. The aim of the current investigation was to prepare and compare the performance of SP loaded nanostructured lipid carrier (SP-NLC) and SP alcoholic gels (SP-ALC) on two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
76
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 26 publications
2
76
0
1
Order By: Relevance
“…The usual daily dose of spironolactone (50‐200 mg/day) did not show serious side effects and can be considered safe for long‐term therapy in FAGA 15 . Kelidari et al reported that the usage of spironolactone as a topical treatment allows high penetration of the drug to the active site with the advantage of minimizing unwanted adverse effects of oral spironolactone 16 …”
Section: Introductionmentioning
confidence: 99%
“…The usual daily dose of spironolactone (50‐200 mg/day) did not show serious side effects and can be considered safe for long‐term therapy in FAGA 15 . Kelidari et al reported that the usage of spironolactone as a topical treatment allows high penetration of the drug to the active site with the advantage of minimizing unwanted adverse effects of oral spironolactone 16 …”
Section: Introductionmentioning
confidence: 99%
“…There are only two published reports on the encapsulation of SP into lipid-based nanocarriers (e.g., solid lipid nanoparticles (SLNs) and nanosctructured lipid carriers (NLCs)) as a potential topical treatment of acne [32,33]. In a randomized, double-blind, prospective trial SP-NLCs and SP-alcoholic gel were able to significantly reduce the mean number of total acne lesions and non-inflammatory lesions [33].…”
Section: Introductionmentioning
confidence: 99%
“…Though SP has traditionally been used as an oral medication, there has been an interest in developing alternative formulations (Abdel-Raouf et al 2021;Abdel-Raouf et al 2020;Biyashev et al 2020;Ilic et al 2021;Kelidari et al 2017;Kelidari et al 2016;Kelidari et al 2015;Salama et al 2019) that can be applied topically on the skin for beneficial purposes and to avoid the systemic effects that usually limit its use to females (Bowman et al 2012). In addition, because glucocorticoids can induce skin atrophy and inhibit wound healing due to aberrant stimulation of mineralocorticoid receptors, SP and related MR antagonists have been employed in experimental studies in mouse models and human subjects to counteract some of the negative effects of glucocorticoids (Boix et al 2018;Maubec et al 2015;Nguyen et al 2016).…”
Section: Introductionmentioning
confidence: 99%